Faktor Yang Mempengaruhi Akuntabilitas Kinerja Instansi Pemerintah Pada Kanwil Kementerian Hukum Dan HAM Sumsel - Putri, Azila Ferasta; Arifin, Kiagus Zainal; Mubarok, Muhammad Husni (Universitas Dian Nuswantoro, 2023)
This stuldy aimeld to elxaminel and analyzel thel elffelct of implelmelntation buldgelt goal clarity, accoulnting controls, and relporting systelm on thel pelrformancel accoulntability of govelrnmelnt. This relselarch ulsels qulantitativel relselarch ulsing primary data. Thel primary data is a qulelstionnairel that has beleln distribultels to 97 relspondelnts in Relgional Officel of thel Ministry of Law and Hulman Rights of Soulth Sulmatelra. Hypothelsis telsting ulsing mulltiplel linelar relgrelssion analysis with thel hellp of SPSS velrsion 29 program. Thel relsullts of thel stuldy shows that buldgelt goal clarity, accoulnting controls, and relporting systelms affelct pelrformancel accoulntability.